X.25 PROTOCOL ON LOCAL AREA NETWORK SYSTEM NERWORK (LAN) - Nur Azizah; Ir. Jalinas Ir. Jalinas (Jurnal Sistem Komputer, 1996)
Network Systems Local Area Network (LAN) is required in the local network system so that the Ministry of Industry Pusdata can use the same database, ease of getting information, developed with the increasing use of distributed processing will be terminal. The number of nodes can be added or subtracted withou t having to disrupt existing operations. The relationship that node, using the method CSMA / CD, where CSMA / CD can detect an incoming channel. In data communication systems, communication protocols determine the method of operation and system reliability .